Intercultural Issues of the Tourist Offer - Cristina Elena Albu (CES Working Papers, 2015)
Tourism is an opportunity for people from different cultures to meet and interact, to exchange ideas, traditions and ways of thinking. In this industry it is very easy to judge a person just after taking an overall look and studying her general behavior. The aim of this article is to determine the intercultural issues that can show up during the tourist act, while people belonging to different cultures interact. The research method used for creating this article is documentary study. The tourist offer shall be adapted to different types of tourist, taking into consideration some aspects as tourists' behavior, the type of tourism they prefer and, most of all, the culture they belong to and the culture of the people from the place they visit. Despite the immense diversity of our minds, there is a structure that can serve as a basis for mutual understanding.
Keywords: M19; Z19; 330; tourist offer; interculturality; stereotypes; mental soft; cultural shock